The Influence of Bank Soundness Level Based on Risk-Based Bank Rating in Financial Distress in Sharia Banking (Empirical Study of Indonesian Sharia Commercial Banks for the 2018-2020 Period) - Sugianto Sugianto; Hotbin Hasugian; Anzari Ahmad S. (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Considering that the bankruptcy of a bank is marked by financial distress, if these conditions are not known quickly, then financial distress will occur and will continue to bankruptcy or liquidation. Based on this, it is possible for banks to anticipate this by analyzing the level of bank soundness based on the Risk-Based Bank Rating method and looking at Financial Distress using the Modified Altman model prediction analysis (Z-Score). This study aims to determine the effect of the soundness level of Islamic banks on Financial Distress based on the financial ratios in the financial reports and GCG reports in the Modified Altman model (Z-Score). The research method used is a descriptive analysis method with a quantitative approach. The population of this study is all Sharia commercial banks for the 2018-2020 period officially registered on the Financial Services Authority website, totaling 14 Sharia banks. The sampling technique uses financial and GCG report data and calculations using the modified Altaman formula (Z-Score). The analysis technique used is a descriptive test, panel data regression test, classic assumption test, and hypothesis test which aims to determine the effect of a bank’s soundness level on Financial Distress. The results of this study indicate that there are several important financial ratios in 2018-2020 that do not have a significant relationship with financial distress, namely FDR, ROA, GCG, and those that are related, namely NPF and CAR. Meanwhile, Financial Distress is simultaneously related to NPF, FDR, ROA, CAR, and GCG.